Nuclear translocation of nuclear factor of activated T cells (NFAT) as a quantitative pharmacodynamic parameter for tacrolimus. Issue 12 (17th October 2013) - Maguire, Orla; Tornatore, Kathleen M.; O'Loughlin, Kieran L.; Venuto, Rocco C.; Minderman, Hans
Abstract Nuclear factor of activated T cells (NFAT) is a family of transcription factors involved in regulating the immune response. The canonical NFAT pathway is calcium‐dependent and upon activation, NFAT is dephosphorylated by the phosphatase, calcineurin. This results in its translocation from the cytoplasm to the nucleus and transcription of downstream target genes that include the cytokines IL‐2, IL‐10, and IFNγ. Calcineurin inhibitors including tacrolimus inhibit the NFAT pathway and are used as immunosuppressants in transplant settings to prevent graft rejection. There is, as yet, no direct means to monitor tacrolimus pharmacodynamics. In this study, a rapid, quantitative, image cytometry‐based measurement of nuclear translocation of NFAT1 is used to evaluate NFAT activation in T cells and its tacrolimus‐induced inhibition. A strong dose‐dependent correlation between NFAT1 inhibition and tacrolimus dose is demonstrated in vitro. Time kinetic analysis of NFAT1 inhibition in plasma from stable renal transplant recipients before and after an in vivo dose with tacrolimus correlated with the expected pharmacokinetic profile of tacrolimus. This was further corroborated by analysis of patients' autologous CD4 and CD8 T cells. This is the first report to show that the measurement of NFAT1 activation potential by nuclear translocation can be used as a direct, sensitive, reproducible and quantitative pharmacodynamic readout for tacrolimus action. These results, and the rapid turnaround time for this assay, warrant its evaluation in a larger clinical setting to assess its role in therapeutic drug monitoring of calcineurin inhibitors. © 2013 International Society for Advancement of Cytometry